Faculty Unionization and Salary Differentials in Ontario Universities - Skolnik, Michael L.; Woodford, Geraldine (Canadian Journal of Higher Education, 1987)
This paper explores the impact of unionization on salary differentials among Ontario universities by comparing the trends in average salaries between those institutions which have certified bargaining units and those which do not. The principal time period considered is from 1975, when the first Ontario university became certified, to 1983, three years after the most recent faculty association to become certified did so. The age-adjusted average salary increase for the unionized institutions was found to be only about two per cent greater than for the nonunionized group. As well, other data presented led to the conclusion that unionization has not had a significant impact upon relative salary structures in Ontario universities. This conclusion is qualified by noting that certification may not be an effective indicator of unionization, that the presence of unions in some universities may have influenced the salary behaviour of the nonunionized institutions, and that the potential influence of faculty unions was constrained by wage controls and funding limits during the period under investigation.